Synthesis of Cationic Waterborne Polyurethanes from Waste Frying Oil as Antibacterial Film Coatings - Sivaphol Phunphoem; Onusa Saravari; Pitt Supaphol (International Journal of Polymer Science)
Cationic waterborne polyurethane (CWPU) was synthesized from waste frying oil and utilized as antibacterial film coatings. Waste oil-based monoglyceride was synthesized by the alcoholysis reaction of waste oil with glycerol, while CWPUs were prepared by esterification with methylenediphenyl 4,4′-diisocyanate (MDI) and bis(2-hydroxyethyl)dimethyl ammonium chloride (BHMAC) as an internal emulsifier. The effect of internal emulsifier contents on the chemical structures and properties of the obtained polyurethanes was studied. Bactericidal activity of the obtained polyurethanes toward Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) was investigated using the time kill assay. CWPUs were successfully synthesized as confirmed by proton nuclear magnetic resonance spectroscopy (1H-NMR) and Fourier transform infrared spectroscopy (FT-IR). Effects of the internal emulsifier on particle size of CWPUs and mechanical properties of the resulting polyurethane films were investigated and measured by transmission electron microscopy (TEM). Particle size diameter of CWPUs ranged from 13.38 to 28.75 nm. The resulting polyurethane films were very pliable, with moderate adhesion and hardness. All films showed good resistance to water and diluted acid but poor resistance to dilute alkali. Obtained CWPUs provided excellent antibacterial activity, with efficiency increasing with increasing amount of BHMAC. Interestingly, antibacterial ability against S. aureus was more rapid than that against E. coli under similar conditions. Results offered an alternative utilization of waste frying oil as a sustainable raw material for the preparation of value-added polymers in the chemical industry.